Those beyond the wall - Johnson, Micaiah (Del Rey, 2024)
"In Ashtown, a rough-and-tumble desert community, the Emperor rules with poisoned claws and an iron fist. He can't show any sign of weakness, as the neighboring Wiley City has spent lifetimes beating down the people of Ashtown and would love nothing more than its downfall. There's only one person in the desert the Emperor can fully trust--and her name is Scales. Scales is the best at what she does: keeping everyone and everything in line. As a skilled mechanic--and an even more skilled fighter, when she needs to be--Scales is a respected member of the Emperor's crew, who's able to keep things running smoothly. But the fragile peace Scales helps to maintain is fractured when a woman is mangled and killed before her eyes. Even more incomprehensible: There doesn't seem to be a murderer. When more bodies start to turn up, both in Ashtown and in the wealthier, walled-off Wiley City, Scales is tasked with finding the cause--and putting an end to it by any means necessary. To protect the people she loves, she teams up with a frustratingly by-the-books partner from Ashtown and a brusque-but-brilliant scientist from the City, delving into both worlds to track down an invisible killer. But the answers Scales finds are bigger than she ever could have imagined, leading her into the brutal heart beneath Wiley City's pristine fȧade and dredging up secrets from her own past that she would rather keep hidden. If she wants to save the world from the earth-shattering truths she uncovers, she can no longer remain silent--even if speaking up costs her everything."